INDUKSI BIAK KALUS DAN BIAK SUSPENSI SEL Aquilaria malaccensis Lam. - Aryani Leksonowati; Witjaksono Witjaksono; Diah Ratnadewi (BERITA BIOLOGI, 2017)
Aquilaria malaccensis Lam. is a plant species producing fragrant woody material that contains some resin. The compounds can be used as medicine and perfume. Sesquiterpenoid, one group of compounds has been found being synthesized and subsequently extracted from callus and cell suspension culture of Aquilaria species. The aim of this research was to find a method of producing friable calli and cell suspension cultures from leaves or internodes of A. malaccensis in vitro by using suitable plant growth regulators; cell suspension that will suitably serve as material to produce sesquiterpenoid afterwards. Calli were established in almost all treatments of auxin-cytokinin on both leaves and internod explants. The treatment of 10 mg/L IBA induced the highest percentage of callus coverage from leaves with a rather compact structure. The combined treatment of 1–2 mg/L 2.4-D and 0.2–0.3 mg/L BA induced friable callus formation in more than 80% of cultures with 27–32% callus coverage percentage.  The use of 2,4-D induced a better formation of cell suspension than Picloram, with maximum volume up to 7 mL. Cell suspension culture with fine and homogenous aggregate could be established in the medium supplemented with 0.5 –1 mg/L 2,4-D.